The Correlation of Learning Dependence and Creativity with Learning Achievement in Social Science - Ansori, Isa; MuslimatunDewi, Indah; Ahmadi, Farid; Fathurrahman; Permata Hapsari, Intan (International Journal of Psychosocial Rehabilitation, 2019)
This study aims to test the correlation of learning independence and creativity with learning achievement in social science of the fourth graders at SDN Gugus Dwija Harapan Semarang. This study was a correlational study employing a quantitative type. The techniques of data collection were interview, questionnaire, and documentation. The data analysis of this study was descriptive analysis, prerequisite test analysis, and hypothesis test. The results showed that there was a positive and significant correlation of learning independence with learning achievement of social science of the fourth graders SDN Gugus Dwija Harapan Semarang, which was indicated by r=0.785 with the significance less than 0.05, there was a positive and significant correlation of creativity with learning outcomes of social sciences, indicated by r=0.718 with the significance less than 0.05, there was a positive and significant correlation of learning dependence and creativity with learning achievement of social sciences, indicated by r=0.851 with the significance less than 0.05. Based on the research data, learning independence and creativity are factors affecting students’ achievement in social sciences.